The congenital abnormalities and malformations contained in Ricardo Palma’s «La astrología en el Perú» - Alave Toribio, Alisson Ariana (2022)
This article will analyze the congenital anomalies and malformations that are evidenced in the story «La astrología en el Perú», where the illustrious Don Ricardo Palma describes the explanations for the deformities with which newborns were born in the 17th century, which were based on the mothers, ignorance of astrology. This work aims to explain these alterations scientifically, based on three branches of medicine: genetics, embryology, and neonatology. In addition, it seeks to inform about the diagnoses that medical astrology used to use based on superstitions, in comparison with contemporary medicine that opts for specialized research to detect the conditions that the fetus could suffer from its intrauterine development.